2008
DOI: 10.1007/s00415-008-0997-1
|View full text |Cite
|
Sign up to set email alerts
|

Grey and white matter loss along cerebral midline structures in myotonic dystrophy type 2

Abstract: Myotonic dystrophy type 2 (DM2) is an autosomal dominantly inherited multisystemic disorder and a common cause of muscular dystrophy in adults. Although neuromuscular symptoms predominate, there is clinical and imaging evidence of cerebral involvement. We used voxel-based morphometry (VBM) based on T1-weighted magnetic resonance images to investigate brain morphology in 13 DM2 patients in comparison to 13 sex-and age-matched controls. Further, we employed novel computational surface-based methods that specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…Central nervous system involvement in DM1 implicates cognitive impairment, hypersomnolence, and personality and behavioral disturbances (Abe et al, 1994;Delaporte, 1998;Meola et al, 2003;Modoni et al, 2008;Turnpenny et al, 1994). Grey matter reduction has also been described in various cortical regions, the hippocampus and the thalamus of DM1 patients (Minnerop et al, 2008;Minnerop et al, 2011;Weber et al, 2010). At the molecular level, nuclear aggregation of mutant mRNAs in combination with MBNL1 has been described in cortical and subcortical neuronal cells of DM1 patients post-mortem (Jiang et al, 2004).…”
Section: Defect Of Mtor Signaling Pathway In Dm1 1769mentioning
confidence: 99%
“…Central nervous system involvement in DM1 implicates cognitive impairment, hypersomnolence, and personality and behavioral disturbances (Abe et al, 1994;Delaporte, 1998;Meola et al, 2003;Modoni et al, 2008;Turnpenny et al, 1994). Grey matter reduction has also been described in various cortical regions, the hippocampus and the thalamus of DM1 patients (Minnerop et al, 2008;Minnerop et al, 2011;Weber et al, 2010). At the molecular level, nuclear aggregation of mutant mRNAs in combination with MBNL1 has been described in cortical and subcortical neuronal cells of DM1 patients post-mortem (Jiang et al, 2004).…”
Section: Defect Of Mtor Signaling Pathway In Dm1 1769mentioning
confidence: 99%
“…Previous magnetic resonance imaging (MRI) studies of adult-onset DM1 have revealed evidence of atrophy (cortical, brainstem, and callosal) and white matter lesions (Censori, Provinciali et al 1994; Hashimoto, Tayama et al 1995; Bachmann, Damian et al 1996; Martinello, Piazza et al 1999; Antonini, Mainero et al 2004; Minnerop, Luders et al 2008; Romeo, Pegoraro et al 2010). Volumetric changes, including ventriculomegaly and callosal hypoplasia, have also been observed in the childhood-onset form (Glantz, Wright et al 1988; Hashimoto, Tayama et al 1995; Martinello, Piazza et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The most common brain changes seen in magnetic resonance imaging (MRI) studies of both early-onset and adult-onset DM1 have been ventricular enlargement, cortical atrophy, and white matter hyperintensities [8, 14, 2024]. Previous studies have illustrated a very wide range in severity of brain involvement in this disease and some studies, but not all, have shown associations between imaging abnormalities and cognitive function [14, 21, 25].…”
Section: Introductionmentioning
confidence: 99%